A Pharmacovigilance Study on Adverse Drug Reaction Profile at a Tertiary Care Teaching Hospital from Western Part of India - Doshi, Nirali; Prajapati, Bijal; Selvaraj, Lavanya (International Journal of Pharmaceutical Investigation, 2025)
Background Pharmacovigilance studies analyzing Adverse Drug Reactions (ADRs) play a crucial role in understanding the ADR profile at tertiary care centers. The objective of this study is to identify, analyze and understand the ADR profile and contribute to the Pharmacovigilance Programme of India (PvPI) mission of drug and patient safety. Materials and Methods This observational study was conducted from July 2022 to December 2023 at a tertiary care teaching hospital, following Institutional Ethics Committee approval. Data were collected using the Central Drug Standard Control Organization (CDSCO) ADR reporting form. ADRs were characterized based on patient demographics, drug class, system organ class, seriousness, outcome and causality using descriptive statistics. Results A total of 125 ADRs were reported during the study period. The most affected population included females (60.44%) and individuals aged 18-65 years (73.65%). Antibiotics were most commonly associated with ADRs (28.8%). The majority of ADRs were classified as non-serious (62.6%). Causality assessment according to the World Health Organization Uppsala Monitoring Centre (WHO-UMC) criteria revealed that 50.4% of ADRs had a probable correlation, 48.8% had a possible correlation and 0.8% had an unlikely correlation to the suspect drug. Conclusion This study highlights key aspects of ADR analysis and provides insights into the ADR profile at the tertiary care center. Pharmacovigilance studies are essential for addressing underreporting in busy hospitals and improving the culture of ADR reporting. Further research focusing on maternal and fetal exposure as well as medication errors is needed within the Indian healthcare system.
Keywords: ADR; Drug safety; MedDRA; PvPI